Pro statu et incolumnitate regni mei: royal monastic patronage 1066–1154 - Mason, Emma (Studies in church history, 1982)
Dangers to the cohesion of the Anglo-Norman regnum correlate to a marked extent with the fluctuating patronage extended by the Anglo-Norman kings towards Westminster Abbey, and other religious houses, in their search for one which would symbolize and enhance the stability of their dynasty.Westminster itself had royal connections from the outset. The original church of St Peter, on Thorney Island in the Thames, to the west of London, was founded by Saebert, king of the East Saxons, and his wife Ethelgoda.’ The couple were allegedly buried there early in the seventh century, but it was some four hundred and fifty years before further royal burials took place in St Peter’s The church was restored by Offa of Essex in the early years of the eighth century, and c959 king Edgar sold it to Dunstan, who founded a monastery on the site. Edgar gave several manors to this abbey, and Aethelred II gave or confirmed others. Less exalted donors followed suit, and the house was already fairly prosperous when Harold I Harefoot was buried there in 1040. His successor and half-brother Harthacnut, is said to have had his body thrown out.